A New Efficient Method for Solving Two-Dimensional Burgers' Equation. (13th August 2012) - Aminikhah, Hossein
Abstract : We introduce a new hybrid of the Laplace transform method and new homotopy perturbation method (LTNHPM) that efficiently solves nonlinear two-dimensional Burgers' equation. Three examples are given to demonstrate the efficiency of the new method.